Analysis and Decomposition for Improved Convergence of Nonlinear Process Models in Chemical Engineering1. Issue 11 (10th October 2017) - Bublitz, Saskia; Esche, Erik; Tolksdorf, Gregor; Mehrmann, Volker; Repke, Jens‐Uwe
Abstract: Solving nonlinear equation systems as they occur in process simulation simultaneously, often fails due to ill‐conditioned models or bad initialization. To counteract these issues two methods have been implemented in the web‐based platform MOSAICmodeling. The Dulmage‐Mendelsohn algorithm forms a block diagonal Jacobian matrix. In addition, the bordered block transformation identifies variables that need to be carefully initialized due to their great influence on the system. Both methods are applied on two process models and their convergence and sensitivity towards initialization is analyzed. Abstract : The simultaneous solution of nonlinear equation systems frequently fails due to ill‐conditioned model formulations or badly chosen initial values. To counteract these problems two methods have been implemented in MOSAICmodeling: the Dulmage‐Mendelsohn algorithm and the bordered block transformation.